Induksi Kalus Eksplan daun Tanaman Anggur (Vitis vinivera L.) dengan Aplikasi 2,4-D Secara in Vitro - ROLIANA VITASARI PURBA; HESTIN YUSWANTI; I NYOMAN GEDE ASTAWA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2017)
Induction can Callus Eksplan the Vine (Vitis vinivera L.) With The Application 2,4-D in In Vitro This research aims to find the influence of the provision of 2,4-D concentration on the growth of the explant callus of grapevine leaves by in vitro treatment and to know how much the concentration of the provision of 2,4-D needed to the shape and growth of explant callus of vine leaves. This research was conducted in April until August 2016 in the Laboratory of Plant Tissue Culture, Program Study Agroekoteknologi, Faculty of Agriculture, Udayana University. The method used was Complete Random Method (CRM). The variable observed in this research was when the explant got curvy, the total percentage of the curving explant, when the explant got swollen, percentage of the swollen up explant and the percentage of brownish explant. Influence of the ZPT 2,4-D provision gives real influence to the observed variable to the variable when the explant got curvy and the percentage of brownish explant, affects really real to the total percentage of the curved explant.MS + 1,5 ppm 2,4-D treatment gives the best growth seen at the variable when the explant curves the fastest (2,4 days), the highest percentage of the curved explant (93,3%) and the highest percentage of the swollen explant (20,0%). This treatment which successfully creates is 1,5 ppm 2,4-D treatment.